(untitled) - Kirn, Elaine (New York, 1996)
Interactions One: A Communicative Grammar, 3/e, introduces, practices, and builds on the content, structures, and vocabulary presented in the companion books. The presentation of grammar in context provides students with useful examples of when to use key structures and new vocabulary.Ideal for beginnig to high-beginning students.
Keywords: English language,English language,Listening; Spoken english,Textbooks for foreign speakers,Problems, exercises, etc